2012
DOI: 10.1007/s10570-012-9672-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk chemical analysis of the durability of an easy care finish on cotton

Abstract: The wash durability of the easy care finish Dimethylol Dihydroxyethylene Urea (DMDHEU) on cotton fabric under ISO 105 CO6 and CO9 test conditions and extended domestic laundering conditions was investigated by surface and bulk sensitive techniques, in particular X-ray photoelectron spectroscopy, elemental analysis and crease recovery angle performance. The presence of the finish was detected at the fibre surface through the N (1 s) photoelectron signal and saturation of the fibre surface with finish was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…When the DMDHEU treated cotton fabric was laundered both with/without perborate there were marginal decreases in the CRA performance in the concentration range of 60 -100 g/L DMDHEU, but the decrease did not reach the level of the control cotton fabric (0 g/L DMDHEU). This observation agrees with the previously reported information that the DMDHEU is durable even after extended laundering [21]. While the decrease in CRA performance with the number of washes was relatively small in the 0 -100 g/L range, the decrease was more obvious at the 140 g/L DMDHEU application level, Figure 1.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…When the DMDHEU treated cotton fabric was laundered both with/without perborate there were marginal decreases in the CRA performance in the concentration range of 60 -100 g/L DMDHEU, but the decrease did not reach the level of the control cotton fabric (0 g/L DMDHEU). This observation agrees with the previously reported information that the DMDHEU is durable even after extended laundering [21]. While the decrease in CRA performance with the number of washes was relatively small in the 0 -100 g/L range, the decrease was more obvious at the 140 g/L DMDHEU application level, Figure 1.…”
Section: Resultssupporting
confidence: 92%
“…Previous research has demonstrated that crosslinking of cotton fabrics with DMDHEU concentrations at lower than 140 g/L favours tri-and tetra-functional crosslinks and the crosslinks are stable to extended laundering. However DMDHEU application at 140 g/L is dominated by unstable bi-functional crosslinks [21]. Hence the measurable decrease in CRA performance, bending and shear properties of the cotton 140 g/L DMDHEU treated, washed cotton fabric may be explained by the bi-functional crosslinks which are unstable to repeated Wascator washing and are prevalent at this higher application levels.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1). During application of the easy-care finishes, it is the hydroxyl groups of the amorphous fraction of the cellulose polymer that are modified, which implies that the application of easy-care finishes affects the accessibility of the cellulose material to various chemicals such as dyes and solvents (Haule et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous work by Haule et al (2012) on the durability of the easy-care finish on cotton fabrics toward extended domestic laundering, it was demonstrated that the easy-care finishes are durable to domestic laundering for the entire lifecycle of the garment. This clearly implies that it will be necessary to remove the easy-care finishes from the garments in order to make possible the dissolution of the waste cotton garments in NMMO solution during the commercial production of the regenerated lyocell-type fibres.…”
Section: Introductionmentioning
confidence: 99%